Pola Komunikasi Pimpinan Cabang Ikatan Pelajar Nahdlatul Ulama’ (Ipnu) Kabupaten Ponorogo Dalam Menanggulangi Radikalisme - Ahmad Faizin Ngajibullah; Kha Fidhoh (Journal of Communication Studies, 2023)
This study aims to find out how the leaders of the Nahdlatul Ulama 'Student Association branch in Ponorogo Regency to counteract radicalism and to know the communication applied by the leaders of the Nahdlatul Ulama' Student Association Branch of Ponorogo Regency in Overcoming Radicalism. This study uses a qualitative approach which has the characteristics of direct data sources, the description is the delivery of communication patterns of the PC leadership of IPNU Ponorogo. The results of this study are the ways of the leadership of PC IPNU Ponorgo in warding off radicalism, namely by providing knowledge of the dangers of radicalism, especially for students through various media. existing and existing activities in PC IPNU Ponorogo, besides that PC IPNU Ponorogo leaders also gave examples to cadres of tolerance and respect for traditions that already exist in Ponorogo district. And the communication patterns used are primary, secondary, literal, and circular communication. And there is also communication carried out by the leadership of the PC IPNU Ponorogo, namely by mass communication and group communication, this communication is carried out by providing information about radicalism through seminars, studies and information obtained by PC IPNU Ponorogo leaders broadcast to IPNU cadres via the Whatss group app